1999
DOI: 10.1046/j.1365-2362.1999.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant protein A binds to Cryptococcus neoformans without promoting phagocytosis

Abstract: Our results indicate that SP-A binds in a concentration-dependent manner to both encapsulated and acapsular C. neoformans. Despite SP-A binding to the acapsular C. neoformans, phagocytosis by various phagocytes was not enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…These results were unexpected as it has previously been reported that SP-D does not bind to capsular C. neoformans (35,43). The exact cause of the differences between the data obtained in the present study and those in previous reports is as yet unclear but may be related to differences in sensitivities of the antibodies used (35) or the different experimental approaches to the detection of bound protein (43).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…These results were unexpected as it has previously been reported that SP-D does not bind to capsular C. neoformans (35,43). The exact cause of the differences between the data obtained in the present study and those in previous reports is as yet unclear but may be related to differences in sensitivities of the antibodies used (35) or the different experimental approaches to the detection of bound protein (43).…”
Section: Discussioncontrasting
confidence: 89%
“…Based on previous studies (35,43), the finding that SP-D had the highest affinity for the acapsular mutant of C. neoformans (strain B4131) was as expected. On the other hand, SP-D did also bind to the encapsulated strains but with much lower affinity.…”
Section: Sp-d Binds Encapsulated As Well As Acapsular C Neoformanssupporting
confidence: 76%
See 1 more Smart Citation
“…SP-A has been shown to inhibit TNF-␣ synthesis induced by LPS-stimulated cells (24), but can also independently stimulate TNF-␣ production (25). Moreover, SP-A binds to LPS (26) and to the surface of a variety of bacteria (27,28), viruses (29), and fungi (30) and enhances the phagocytosis of some micro-organisms (31), but inhibits (32) or does not affect the phagocytosis of others (33).…”
mentioning
confidence: 99%
“…For instance, it is claimed that for some organisms, collectins suppress phagocytosis; other studies suggest that SP-A and SP-D have opposite effects on host cell function (9). In addition, the functional comparisons between the lung collectins and MBP are clearly limited, since there have been no reports of complement activation by SP-A or SP-D.…”
Section: Surfactant Proteins and Pulmonary Host Defensementioning
confidence: 99%